2012
DOI: 10.5121/ijwmn.2012.4102
|View full text |Cite
|
Sign up to set email alerts
|

Multiuser Detection in Asynchronous Multibeam Communications

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, there is a need to establish a balance between improved signals and noise reduction systems such that the cost of detection and risk of missing the target will be carried out at a minimum possible cost. These include detection-interpolation scheme [13], penalty function technique [14], minimax noise variance estimation [15], performance improved nonlinear detector of spread spectrum receiver [16], nonparametric dynamic model for monitoring changes in signal detection performance [17], synthetic antenna array concept for signal detection enhancement [18], algorithm based on sparsity hypotheses [19], successive interference cancellation architecture and channel decoding to treat the co-channel interference [20], Dynamic Spectrum Access (DSA,) [21], and orthogonal frequency division multiplexing scheme for fading/interference mitigation [7,8]. Apart from Broumandan [18] that carried out research on enhancement of signal detection using synthetic antenna array concept, scanty studies were identified in applying the component-based circuitry for the enhancement of signal detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a need to establish a balance between improved signals and noise reduction systems such that the cost of detection and risk of missing the target will be carried out at a minimum possible cost. These include detection-interpolation scheme [13], penalty function technique [14], minimax noise variance estimation [15], performance improved nonlinear detector of spread spectrum receiver [16], nonparametric dynamic model for monitoring changes in signal detection performance [17], synthetic antenna array concept for signal detection enhancement [18], algorithm based on sparsity hypotheses [19], successive interference cancellation architecture and channel decoding to treat the co-channel interference [20], Dynamic Spectrum Access (DSA,) [21], and orthogonal frequency division multiplexing scheme for fading/interference mitigation [7,8]. Apart from Broumandan [18] that carried out research on enhancement of signal detection using synthetic antenna array concept, scanty studies were identified in applying the component-based circuitry for the enhancement of signal detection.…”
Section: Introductionmentioning
confidence: 99%